Composites with pineapple-leaf fibers manufactured by layered compression molding (2016)
(Eng) Compression molding process was used to manufacture composites reinforced with pineapple-leaf fibers. During manufacturing, four plies of polypropylene with an average thickness of 0.76 mm were used and the fibers were equally distributed between plies to generate a stacked composite with the fibers in external layers transversally oriented to those in the inner layer. Two types of pineapple-leaf fibers were used as reinforcement: untreated fibers and fibers modified in an alkali solution (10% NaOH). Two different fiber contents were also evaluated in order to measure their effect on the mechanical properties of the composite. Ultimate tensile strength, strain at maximum load, Young's modulus, flexural strength and flexural modulus were measured. Tensile strength was increased 22% and Young's modulus increased 60%. Flexural strength and flexural modulus increased 19 % and 50% respectively, with fiber content. However, the alkali treatment did not improve those properties. Fractured surfaces of the composites were examined using electron microscopy and failure mechanisms such as fiber pullout and matrix deformation were observed.